Lysozyme Gene Expression in 3T3-L1 Cells Sustains Expression of Adipogenic Genes and Adipocyte Differentiation - Lluch, Aina; Latorre, Jessica; Fernández-Real, José Manuel; Moreno-Navarrete, José María (Frontiers in Cell and Developmental Biology, 2022)
Substantial levels of lysozyme in adipose tissue in association to obesity have been recently demonstrated in mice and humans. In addition, experiments in mice suggest that lysozyme might impact on adipose tissue adipogenesis. To further investigate the relationship between lysozyme and adipogenesis, in the present study, we aimed to study lysozyme (Lyz2) during 3T3-L1 adipocyte differentiation and its possible role in adipogenesis. Time course experiment during 3T3-L1 adipocyte differentiation indicated that Lyz2 gene expression decreased at day 4, which was caused by isobutylmethylxanthine administration, and recovered at the end of the process (day 8). Importantly, the impact of isobutylmethylxanthine-induced downregulation of Lyz2 gene expression on adipogenesis was not comparable to that observed in the full cocktail, questioning whether the reduction in lysozyme at early stage of adipocyte differentiation is relevant to this process. In fact, the depletion in Lyz2 expression had a negative impact on adipogenesis, and rosiglitazone administration failed to compensate for the anti-adipogenic effect observed in Lyz2 gene knockdown cells. Otherwise, when Lyz2 gene KD cells were co-cultured with control cells, these cells had higher expression of adipogenic genes than those co-cultured with themselves at the end of adipocyte differentiation. In conclusion, this study suggests that lysozyme expression in 3T3-L1 cells sustains expression of adipogenic genes and adipocyte differentiation.